2021
DOI: 10.1080/00952990.2021.1927066
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the supply of alcohol to adolescent daughters and sons

Abstract: Background: Parents are the main supplier of alcohol to children but it is not known whether mothers and fathers equally contribute to the supply of alcohol to their female and male children as these children transition to adulthood. Objectives: i) to determine whether the gender of the parent is associated with the gender of the adolescent offspring when alcohol is supplied and ii) whether the gender of the parent supplying is associated with gender differences in adolescent binge drinking and alcohol related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Studies that reported prevalence rates for all minors, all found prevalence rates higher for those who were older (indicated by either age in years or school grade) ( Health and Social Care Information Centre, 2011 , 2013 , 2015 , 2017 ; Stafström, 2014 ; Shaw et al, 2018 ); ranging between 32.0 and 38.0% for those who were 15 versus 4.0–8.0% for those who were 11 years old ( Figure 2 ). The Australian Parental Supply of Alcohol Longitudinal Study (APSALS) ( Aiken et al, 2017 ; Mattick et al, 2017 ; Mattick et al, 2018 ; Clare et al, 2019 ; Aiken et al, 2020 ; Boland et al, 2020 ; Clare et al, 2020 ; Najman et al, 2021 ) also found that prevalence rates increased with age from 9.3% in 2010–11 (mean age: 12.9 years) to 10.5% in 2013–14 (mean age: 15.8 years) for all minors who reported parents as their only alcohol source, and from 15.2% in 2010–11 to 45.7% in 2014–15 (mean age: 16.9 years) for those reporting any parental supply (i.e. including those additionally reporting supply via other sources).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that reported prevalence rates for all minors, all found prevalence rates higher for those who were older (indicated by either age in years or school grade) ( Health and Social Care Information Centre, 2011 , 2013 , 2015 , 2017 ; Stafström, 2014 ; Shaw et al, 2018 ); ranging between 32.0 and 38.0% for those who were 15 versus 4.0–8.0% for those who were 11 years old ( Figure 2 ). The Australian Parental Supply of Alcohol Longitudinal Study (APSALS) ( Aiken et al, 2017 ; Mattick et al, 2017 ; Mattick et al, 2018 ; Clare et al, 2019 ; Aiken et al, 2020 ; Boland et al, 2020 ; Clare et al, 2020 ; Najman et al, 2021 ) also found that prevalence rates increased with age from 9.3% in 2010–11 (mean age: 12.9 years) to 10.5% in 2013–14 (mean age: 15.8 years) for all minors who reported parents as their only alcohol source, and from 15.2% in 2010–11 to 45.7% in 2014–15 (mean age: 16.9 years) for those reporting any parental supply (i.e. including those additionally reporting supply via other sources).…”
Section: Resultsmentioning
confidence: 99%
“…For studies reporting prevalence rates by gender for all minors, four out of eight studies (50.0%) found no significant differences in prevalence rates between male and female respondents ( Danielsson et al, 2011 ; Health and Social Care Information Centre, 2011 , 2013 , 2015 ), two studies (25.0%) found slightly higher prevalence rates in females than males ( Strandberg et al, 2014 ; Health and Social Care Information Centre, 2017 ) and one study found slightly higher prevalence rates in males than females ( Murphy et al, 2021 ). Another study ( Najman et al, 2021 ) reported parental supply separated by age and the individual parent who supplied alcohol (i.e. father or mother); boys reported higher rates of supply compared with girls when alcohol was received from the father.…”
Section: Resultsmentioning
confidence: 99%
“…31 A longitudinal study conducted in Australia found that a considerable proportion of children reported being given alcohol by their parents, with the prevalence increasing as children age. 32 While there have been numerous studies investigating the prevalence of alcohol drinking among Chinese adolescents, much of the previous research has focused on eastern or developed regions of China, such as Shanghai and Zhejiang Province. Additionally, the majority of participants in these studies were middle school students.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…In addition, parental alcohol supply is associated with higher rates of alcohol consumption among adolescents 31. A longitudinal study conducted in Australia found that a considerable proportion of children reported being given alcohol by their parents, with the prevalence increasing as children age 32…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation